Liberal Mind of John Morley - Staebler, Warren (Book collections on Project MUSE., 1943)
An unusual study of a distinguished Victorian, approached through the ideas which occupied and actuated his career. By examining John Morley's intellectual interests and the development of his personal philosophy, Mr. Staebler arrives at the essential Morley and the essential Liberal of the late nineteenth century. Originally published in 1943.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.